Short Term Usage of Omega-3 Polyunsaturated Fatty Acids Ameliorate Lipopolysaccharide-Induced Inflammatory Response and Oxidative Stress in the Neonatal Rat Hippocampal Tissue - Shi, Jipeng; wang, Weiwei; Sang, Guimei; Xi, Huifang; Sun, Yazhou; Lu, Chaosheng; Ye, Hezhen; Huang, Limi (Frontiers in Nutrition, 2020)
Objective: To investigate the effect of omega-3 polyunsaturated fatty acids (ω-3 PUFAs) on lipopolysaccharide (LPS)-induced inflammatory response and oxidative stress in neonatal rat brain. Methods: Ninety-six 3-day-old Sprague Dawley rats were divided into four groups: control (saline/saline), LPS/ω-3, LPS/ω-6, and LPS/saline (n = 24/group). All rats, except those in the control group, were treated with ω-3 PUFAs, ω-6 PUFAs, or saline at 15 ml/kg for 1 or 5 consecutive days following the intraperitoneal LPS-challenge (0.6 mg/kg). Rats in the control group underwent the same procedures and received saline (vehicle). After 1 or 5 days of treatment, 12 rats from each group were sacrificed and their hippocampuses were collected. The expression of inflammation-related genes as well as the levels of oxidative stress markers in hippocampal tissues were determined. Results: After 1 or 5 days of treatment, the expression of toll-like receptor 4 and multiple proinflammatory cytokines were significantly decreased in the LPS/ω-3 group compared with those in the LPS/saline group. The activities of superoxide dismutase and glutathione (GSH) were significantly elevated, whereas the levels of malondialdehyde and oxidized glutathione (GSSG) and the ratio of GSSG/GSH were remarkably lowered in the LPS/ω-3 group compared with those in the LPS/saline group after 1 day of treatment. Opposite effects were observed in the LPS/ω-6 group. Conclusion: ω-3 PUFAs may protect rat brain tissue against LPS-induced inflammatory response and oxidative stress.